Analisis Strategi Pembelajaran IPS dalam Mengembangkan Kesadaran Sosial Siswa Sekolah Dasar - Imam Sofian; Junaidin (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to analyze Social Studies (IPS) teaching strategies for developing social awareness among elementary school students based on research findings. This study employs a literature review (library research) using a descriptive qualitative approach. Research data were obtained from various scientific articles, national journals, and literature sources relevant to IPS learning strategies and the social awareness of elementary school students. Data analysis was conducted through data reduction, data presentation, and drawing conclusions regarding the findings of previous studies. The results of the study indicate that effective learning strategies for developing students’ social awareness include Project-Based Learning (PBL), cooperative learning, contextual learning, environment-based learning, group discussions, simulations, and role-playing. These strategies have been proven to enhance empathy, social concern, cooperation, responsibility, critical thinking skills, and students’ active participation in social life. Furthermore, teachers play a crucial role as facilitators in creating a participatory, collaborative, and contextual learning environment. Thus, social studies education serves not only as a means of knowledge transfer but also as a medium for character development and the cultivation of students’ social awareness. This study recommends that teachers optimize the use of active learning strategies.